TRANSIENT-RESPONSE OF NONLINEAR PROTECTIVE DEVICES FOR SUPPRESSION OF LIGHTNING SURGES ON A PAIR-WIRE LINE - 김세윤; 하헌태 (IEICE-INST ELECTRON INFO COMMUN ENG, 1991)
A successive iteration algorithm for estimating the response of a parallel two-wire transmission line terminated by nonlinear protective devices in an external electromagnetic pulse is developed and implemented for numerical simulation. The validity of the presented algorithm is assured by showing that the numerical result for a particular nonlinear impedance characteristics of the protective devices approaches the rigorous solution which is also derived here analytically.